2021
DOI: 10.3390/pathogens10050567
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Weather Conditions and Admissions to the Paediatric Intensive Care Unit for Respiratory Syncytial Virus Bronchiolitis

Abstract: Respiratory syncytial virus (RSV) bronchiolitis is a leading cause of global child morbidity and mortality. Every year, seasonal RSV outbreaks put high pressure on paediatric intensive care units (PICUs) worldwide, including in the Netherlands, and this burden appears to be increasing. Weather conditions have a strong influence on RSV activity, and climate change has been proposed as a potential important determinant of future RSV-related health care utilisation. In this national study spanning a total of 13 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, variation in diurnal temperature range did not affect the risk of in uenza A virus 101 or childhood pneumonia 106 . Likewise, weather conditions did not affect the risk of paediatric intensive care unit admission due to respiratory syncytial virus infection 107 .…”
Section: Resultsmentioning
confidence: 90%
“…However, variation in diurnal temperature range did not affect the risk of in uenza A virus 101 or childhood pneumonia 106 . Likewise, weather conditions did not affect the risk of paediatric intensive care unit admission due to respiratory syncytial virus infection 107 .…”
Section: Resultsmentioning
confidence: 90%
“…Whether these prevalence variations are due to geographic locations and subsequent differences in weather or to the potential consequences of global climate change with variable location impacts is unclear. For instance, a longitudinal investigation in the Netherlands showed that the temperature and global radiation were the most frequently associated weather predictors for disease severity and PICU admissions among children with respiratory viruses [ 18 ]. These factors could partially explain the viral respiratory disease seasonal variations.…”
Section: Discussionmentioning
confidence: 99%
“…These factors could partially explain the viral respiratory disease seasonal variations. However, these factors do not explain the changing annual prevalence in the same location, as these weather factors remain essentially unchanged locally [ 18 ]. By contrast, the potential change in clinical practices, and enhanced utilization of viral diagnostics could be other possible explanations for the increasing detection in developed countries [ [19] , [20] , [21] ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of children in the United States who have been infected with the SARS-CoV-2 virus only experienced a mild illness that did not require hospitalization [ 9 ]. Generally, viral lower respiratory tract infections have a seasonal pattern, resulting in many PICU admissions worldwide, primarily during the winter months [ 10 ]. In late summer 2020, there was concern among the intensivists that there would be an increased burden on the children’s hospitals during the winter months due to the overlap of COVID-19 and seasonal viruses.…”
Section: Discussionmentioning
confidence: 99%